ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA KELAS VIII DITINJAU DARI GAYA KOGNITIF REFLEKTIF-IMPULSIF - Ine Febrianti Habel; Nora Susilowaty (LPPM Universitas Advent Indonesia, 2021)
Mathematical connection ability is one of the most important mathematical skills for students. The ability of mathematical connections can be influenced by cognitive styles. One of the cognitive styles reviewed from conceptual tempo is reflective cognitive style and impulsive cognitive style. The purpose of this study was to find out: 1) the most dominant cognitive styles at low, medium, and high levels of mathematical connection ability and 2) analyze and describe the students' mathematical connection abilities in terms of reflective and impulsive cognitive styles. This type of research is descriptive by using qualitative approach. The subjects in this study were 6 students from grade VIII smp Advent Parongpong and grade VIII SMP Advent II Setiabudi selected based on reflective cognitive style and impulsive cognitive style. Data collection method in the form of written tests and interviews. The results showed the most dominant cognitive styles for the low category were impulsive cognitive styles while students with reflective cognitive styles were most dominant for medium and high categories. Reflective students with high mathematical connection ability are able to achieve all indicators of mathematical connection ability. Reflective students with moderate and low mathematical connection skills are less able to achieve all indicators of mathematical connection ability. Impulsive students with high, medium and low mathematical connection skills are less able achieve all indicators of mathematical connection ability.